Personal concept of chronic illness in rural population-identifying myths and beliefs - Nallagatla, Shakuntala; Nallagatla, Navya; Kamichetty, Nagendra Prasad; Rao, Nallagatla Venkata Ramana (International Journal of Research in Medical Sciences, 2017)
Background: The morbidity of Chronic Renal Failure (CRF) is not only physical but also psychological and social. The study aimed at identifying whether there was any mythological belief in being afflicted with such a chronic illness and the personal concept of a chronic illness. Therefore patients with chronic renal failure were selected for the study. Methods: The study includes two different groups of patients, 25 per group examined at two different places at two different points of time. The two groups attended different hospitals in their local areas. Patients who were suffering from chronic renal failure were examined and selected for the study. In both groups results were obtained based on questions designed to get information on four themes: their economic status, their status of work, their dependency status and their personal concept of the illness. All the patients belong to rural areas and have had less than formal education or no education at all. Results: The most important finding in this study was a belief expressed in five patients (Two males and three female). They believed that indulging in sex in their marital life itself was a cause of the illness. One other female patient who had a bad obstetric history felt that her illness was due to the number of abortions she had. Conclusion: In a country like India especially in rural India where people believe in alternative medicine, magico-religious methods of native healers, it is difficult to convince people to go for a counselling service. They have to be provided such a service after the initial physical treatments have been started. It is essential that a service of such kind is provided free of cost at any level, even in a primary health centre. Where possible it is necessary to use diagnostic tools to designate severity of the problem. Otherwise personal ideas about illness that marital life has caused the disease can reflect adversely on the harmony and quality of life of patients. This study has enough potential to conduct more such studies to identify outcomes of chronic illnesses and design interventions accordingly.